Use of Neuromodulators as Aesthetic Treatment in the Lower Face (Canadian Dermatology Today, 2023)
Neuromodulator treatment is one of the most common non-invasive aesthetic treatments in dermatology. Botulinum toxin A has been established as a safe and effective treatment for the upper face. It is increasingly used beyond the forehead, glabella and peri-ocular region. The purpose of lower face neuromodulator is to soften dynamic rhytids, improve facial expression at rest and with animation, and provide facial contouring. There is significant interplay between the muscles of the lower face for expression and function; therefore, careful administration of botulinum toxin A is necessary to avoid adverse effects. This article reviews off-label botulinum toxin A treatments to the peri-oral region, chin and masseter. For the purposes of the article, all dosing provided is for onabotulinum toxin A.